Peak myocardial work assessment to detect coronary ischemia during dobutamine stress echocardiography - Qamruddin, Salima; Fang, Chen; Kachur, Sergey; Bharwani, Sahil; Elagizi, Andrew; Stewart, Merrill; Morin, Daniel P.; Smiseth, Otto A.; Gilliland, Yvonne E. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPeak global myocardial work efficiency (GWE), a measure of peak global myocardial constructive to wasted work ratio, has been shown to discriminate coronary ischemia during treadmill stress echocardiography (SE). We wanted to assess additive utility of peak global longitudinal strain (GLS), global work index (GWI), and GWE in improving positive predictive value (PPV) of an abnormal dobutamine stress echocardiography (DSE) and calculate cost-savings by avoiding secondary tests.MethodsWe prospectively enrolled patients with abnormal DSE who underwent secondary confirmatory tests to confirm significant CAD as our primary cohort, and measured baseline and peak GLS, GWI, and GWE. We also included a control group with normal DSE results and similar measurements. The cost of secondary testing was used to calculate potential savings.ResultsAmong the 45 patients (71% females, mean age 60 ± 12 yrs.), 9 had significant CAD, 11 had non-significant CAD, and 25 were controls (N). Patients with significant CAD had significantly lower peak GLS [−15 (−17, −12.5) vs. −20 (−22, −19.5)%, p < 0.001], peak GWI [1,057 (810.5, 1,057) vs. 2,245 (1,928.5, 2,961) mmHg%, p = 0.02], peak GWE [82 (74.5, 86.5) vs. 89 [(86, 93.5)%, p = 0.001], and peak GCW [1,618 (1,153.5, 2,003) vs. 2,585 (2,262.5, 3,262) mmHg%, p = 0.02] compared to control. ROC analysis demonstrated peak GWE [AUC 0.76 (0.55, 0.97) p = 0.01] to discriminate coronary ischemia. Incorporating peak GWE of <87% into abnormal DSE interpretation improved PPV from 45% to 81%, resulting in an estimated cost savings of 8,274.00 per screened patient.ConclusionsIncorporating peak GWE into standard DSE interpretation enhanced diagnostic accuracy and reduced the cost of downstream testing.